Reaction-free interface promoting strength-ductility balance in graphene nanosheet/Al composites. (March 2020) - Jiang, Yuanyuan; Tan, Zhanqiu; Fan, Genlian; Wang, Lei; Xiong, Ding-Bang; Guo, Qiang; Su, Yishi; Li, Zhiqiang; Zhang, Di
Abstract: The chemical reaction between graphene and Al matrix plays an important role in determining the interface states and mechanical performances of graphene nanosheet (GNS) reinforced Al matrix composites. In this study, effects of interfacial reaction on the strengthening behaviors of GNS/Al composites were investigated. The formation of reaction products, aluminum carbide (Al4 C3 ), was finely tailored with sintering temperature ranging from 500 °C to 620 °C. Interface microstructure characterizations demonstrated three interface states, which were tight GNS-Al interfaces without carbides, partial reaction GNS-Al4 C3 –Al interfaces with nano-sized carbides, and complete reaction Al4 C3 –Al interfaces with larger carbides. Tensile test results revealed that higher strength and ductility was achieved in the composites with tight and carbide-free GNS-Al interfaces, mainly attributing to the interaction between GNS-Al interface and dislocations, rather than load transfer mechanism. This work may provide a new insight into the interface design and strengthening behaviors in graphene/Al composites. Graphical abstract: Image 1